Silencing of SlDRB1 gene reduces resistance to tomato yellow leaf curl virus (TYLCV) in tomato (Solanum lycopersicum). (31st December 2022) - Huang, Xin; Wei, Jianming; Wu, Dan; Mi, Na; Fang, Sili; Xiao, Yao; Li, Yunzhou
ABSTRACT: Double-stranded RNA-binding proteins are small molecules in the RNA interference (RNAi) pathway that form the RNAi machinery together with the Dicer-like protein (DCL) as a cofactor. This machinery cuts double-stranded RNA (dsRNA) to form multiple small interfering RNAs (siRNAs). Our goal was to clarify the function of DRB in tomato resistant to TYLCV. In this experiment, the expression of the SlDRB1 and SlDRB4 genes was analyzed in tomato leaves by qPCR, and the function of SlDRB1 and SlDRB4 in resistance to TYLCV was investigated by virus-induced gene silencing (VIGS). Then, peroxidase activity was determined. The results showed that the expression of SlDRB1 gradually increased after inoculation of 'dwarf tomato' plants with tomato yellow leaf curl virus (TYLCV), but this gene was suppressed after 28 days. Resistance to TYLCV was significantly weakened after silencing of the SlDRB1 gene. However, there were no significant expression differences in SlDRB4 after TYLCV inoculation. Our study showed that silencing SlDRB1 attenuated the ability of tomato plants to resist virus infection; therefore, SlDRB1 may play a key role in the defense against TYLCV in tomato plants, whereas SlDRB4 is likely not involved in this defense response. Taken together, These results suggest that the DRB gene is involved in the mechanism of antiviral activity.